2017
DOI: 10.1111/ppc.12249
|View full text |Cite
|
Sign up to set email alerts
|

The association of spiritual well-being and depression among patients receiving hemodialysis

Abstract: Healthcare providers should consider spiritual well-being in their assessment and interventions by helping the patients to establish meaning, peace, and faith to reduce patients' depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 34 publications
0
6
0
2
Order By: Relevance
“…This finding is compatible with others in showing divergent validity between the HADS subscales with other related outcomes, emphasizing the distinctive ability of the two‐factor solution of the HADS (Schouten et al, 2019). Others found that spiritual well‐being was negatively correlated with depression using the Patient‐Reported Outcomes Measurement Information System (PROMIS) Emotional Distress‐Depression scale in 158 Jordanians with ESRD (Alradaydeh & Khalil, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is compatible with others in showing divergent validity between the HADS subscales with other related outcomes, emphasizing the distinctive ability of the two‐factor solution of the HADS (Schouten et al, 2019). Others found that spiritual well‐being was negatively correlated with depression using the Patient‐Reported Outcomes Measurement Information System (PROMIS) Emotional Distress‐Depression scale in 158 Jordanians with ESRD (Alradaydeh & Khalil, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…untuk mencapai kesejahteraan spiritual. 13 Meskipun demikian, upaya untuk membantu pasien mencapai kesejahteraan spiritual yang tinggi juga perlu dilakukan. Hal ini dapat dilihat dari rerata kesejahteraan spiritual pasien yang masih dalam tingkat sedang.…”
Section: Mayoritas Responden Menjalani Hemodialisis <5 Tahun Yaitu Se...unclassified
“…11 Terdapat penelitian yang telah membuktikan adanya hubungan antara kesejahteraan spiritual dengan gejala depresi, ansietas, dan stres. [12][13][14] Penelitian Martinez & Custodio 15 pada 150 pasien hemodialisis di Brasil menyimpulkan bahwa kesejahteraan spiritual adalah prediktor kuat dari kesehatan mental, distres psikologi, gangguan tidur, dan gejala psikosomatik. Kesehatan mental yang rendah berhubungan dengan kesejahteraan spiritual yang rendah.…”
unclassified
“…Zhang et al, reported that HD patients had high levels of hope (17). In addition, several studies reported high spiritual scores among HD patients (23)(24)(25). Bovero et al also reported moderate-to-high levels of spiritual experiences among cancer patients (20).…”
Section: Discussionmentioning
confidence: 99%